2008
DOI: 10.1074/jbc.m800442200
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Protein Kinase C (PKC)-dependent and PKC-independent Protein Kinase D Catalytic Activation via Gq-coupled Receptors

Abstract: and Ser 748 is the primary mechanism involved in early phase PKD activation, whereas PKD autophosphorylation on Ser 748 is a major mechanism contributing to the late phase of PKD activation occurring in cells stimulated by GPCR agonists. The present studies identify a novel mechanism induced by GPCR activation that leads to late, PKC-independent PKD activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
100
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 85 publications
8
100
1
Order By: Relevance
“…PKD activation was tracked by immunoblot analysis with three different phosphorylation-site specific antibodies (PSSAs). Activation loop phosphorylation was monitored with two PSSAs that recognize phosphorylation reactions in the conserved activation loop motifs of all three PKD isoforms; recent studies indicate that the anti-PKD-Ser(P) 744 (14). PKD phosphorylation also was tracked with the anti-PKD-Ser(P) 916 PSSA that detects a conserved autophosphorylation site at the C terminus of PKD1 and PKD2, but not PKD3.…”
Section: Resultsmentioning
confidence: 99%
“…PKD activation was tracked by immunoblot analysis with three different phosphorylation-site specific antibodies (PSSAs). Activation loop phosphorylation was monitored with two PSSAs that recognize phosphorylation reactions in the conserved activation loop motifs of all three PKD isoforms; recent studies indicate that the anti-PKD-Ser(P) 744 (14). PKD phosphorylation also was tracked with the anti-PKD-Ser(P) 916 PSSA that detects a conserved autophosphorylation site at the C terminus of PKD1 and PKD2, but not PKD3.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of PKD by novel PKCs in the activation loop is generally considered as a prerequisite for activation. However, a PKC-independent role for PKD3 has been suggested in basal glucose uptake of skeletal muscle cells (35) and more recent studies demonstrated that the rapid PKC-dependent PKD activation is followed by a sustained, PKC-independent phase of catalytic activation (36).…”
Section: Discussionmentioning
confidence: 99%
“…PKD1 catalytic activation within cells leads to its auto-phosphorylation at Ser 916 and Ser 748 (33)(34)(35)(36). Rapid PKC-dependent PKD1 activation is followed by a late PKC-independent phase of activation induced by GPCR agonists (35)(36)(37). Accumulating evidence demonstrates that the PKD family plays an important role in a variety of cellular processes and activities, including cytoskeletal organization, gene expression, cell migration, and proliferation (19).…”
mentioning
confidence: 99%
“…In intestinal epithelial cells, PKD1 activation mediates migration and proliferation both in vitro and in vivo (36,38). Accordingly, multiple growth-promoting stimuli rapidly activate PKD1 catalytic activity in intestinal epithelial cells (23, 36, 38 -40) through activation loop phosphorylation (30,(35)(36)(37). Furthermore, transgenic mice that express elevated PKD1 protein in intestinal epithelial cells display a marked increase in DNA-synthesizing cells in their intestinal crypts and a significant increase in the length and total number of cells per crypt (36).…”
mentioning
confidence: 99%